(untitled) (Texas Journal of Medical Science, 2022)
A decrease in the functional activity of the salivary glands causes a violation of the functions of the oral fluid, the active components of which provide oral homeostasis, the integrity of the mucous membrane, periodontal and hard tissues of the teeth. Review of experimental models of hyposalivation in laboratory animals